Effects of high intensity interval training (hiit) with music on exercise motives and quality of life (qol) in physically inactive young adults - Shian, Foo Kai (2020)
motivation and quality of life in sedentary young adults Factors that contribute to physical inactivity are lack of time and insufficient motivation to engage in exercise. Strategies focusing on exercise programme that are fun and timesaving can bring positive effects to physical and psychology of individuals. The study aims to examine the effect of High Intensity Interval Training (HIIT) with music on exercise motivation and quality of life (QoL) among sedentary young adults. This study employed an interventional, pre- and post-study design. Participants were 20 male and female, aged between 22 to 35 years old (M = 25.5, SD = 3). Participants were divided into two equal groups consist of ten participants, HIIT-Music (HIIT-M) group and HIIT-No Music group (HIIT-NM). Participants in the HIIT-M group performed 12 sessions of exercise while listening to the motivational music, whereas HIIT-NM group performed 12 sessions of exercise without listening to music. The result for QoL indicates that there was no significant difference between the HIIT-M and HIIT-NM. Also, the result on five components of exercise motive shows no significant difference between the HIIT-M and HIITNM. To summarize, listening to music during HIIT did not produce significant effects, however there were increment in term of percentage for QoL and five components of exercise motive between pre- and post-test.